(untitled) (AYUSHDHARA, 2025)
Folliculitis Decalvans (FD) is an infectious condition that affects the hair follicle, presenting as painful papules, scales, and pustules, which, in a later stage, causing baldness with scarring. The main cause of the manifestation of FD includes Staphylococcus aureus infection, causing pustular eruptions associated with scaling. Brief Case Report: The current article describes the case of a 5-year-old female child, who presented in OPD with pustular eruptions with scaling and pruritis over the scalp. Examination of the scalp suggested grouped follicular pustules extending from the fronto-temporal region as a band to the central forelock of the scalp. Gram staining of the pus sample collected confirmed gram-positive bacterial species, and culture of the sample confirmed the presence of S aureus by producing a zone of hemolysis over blood agar. The condition was diagnosed as Raktaja Krmi. The patient was treated with Shamana aushadis (pacifying medications), considering the age. Medicines Saribadyasavam and Gopichandanadi gutika was given internally considering the involvement of Pitta. Murvadi agada was prescribed as a Pachana drug as well as an agada, considering the infective nature of the disease. Scalp cold sponging with Guduchyadi kwatha and Shatadhoutha grita was given for external application. Conclusion: After two weeks, patient was advised for follow-up, and the patient had relief from symptoms of scaling, itching, and the appearance of painful pustules. The case report highlights the efficacy of Ayurvedic management in infectious diseases, which can be effectively followed in managing infectious diseases affecting the scalp.